Parents' Perspectives on Healthy Lifestyle Practices for Special Need Students - Ariff Mu’azzam Ab Halim; Mohd Mokhtar Tahar (Journal of ICSAR, 2022)
This study was designed to examine the difference between healthy lifestyle in terms of balanced diet, physical exercises, emotional and self management among special need students in rural and urban areas. This study is conducted quantitatively by using the questionnaires that are valid and reliable. These questionnaires were adapted from the Healthy Lifestyle Instrument. The sample size of 40 parents from Cheras, Kuala Lumpur were participated for the urban area, while another size of 40 parents from Sabak Bernam, Selangor were participated on behalf of the rural area. Google form was used as the platform of the questionnaires and were distributed accordingly online. Inference analysis was used to study the research questions by using Statistical Package for the Social Sciences (SPPS) version 23.0. The analysis showed there was no significance in the difference between special need students in urban area and rural area towards their healthy lifestyle based from the three aspects. As a result, the main party should be obligated in adding healthy lifestyle practices among special need students in both urban and rural areas.